Wood to Energy: Woody Biomass Conversion Technologies - Jessica Tomasello; Lauren McDonell; Martha C. Monroe; Annie Oxarart (EDIS)
FOR-222, a 4-page illustrated fact sheet by Jessica Tomasello, Lauren McDonell, Martha C. Monroe, and Annie Oxarart, is part of the Wood to Energy series. It describes current technologies and those that are being developed to convert wood to energy. Includes references. Published by the UF School of Forest Resources and Conservation, June 2009.